Book Review: The Lessons of Resistance Economy based on the Thought of the Supreme Leader - Allah Morad Seif (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The idea of a resistance economy, proposed by the Supreme Leader of the Islamic Republic of Iran, and his request to explain this idea by academics, has spurred many efforts since 2010, and many products have been published in the form of books, scientific articles, and lectures, but the main question is how far the theory of resistance economy has been successful. This paper examines the answer to the question by focusing on the book "The Lessons of Resistance Economy” by Adel Paygami and has pointed out that there are still many areas that remain vague in the theory of resistance economy. First, the introduction and review of the overall work have been done in the form of each chapter of the book. Then, in criticizing the theme of the work, the eight titles include the definition of a resistance economy, the state and the market, the people based economy, domestic production and national production, sub-systems of the resistance economy, the relative or absolute stability of the economy, economic independence, and growth and justice have been explored. In each of these topics, it has been shown that there are important points that have been less relevant in the publications of resistance economy and in particular in the book.